1995
DOI: 10.1590/s0102-311x1995000100011
|View full text |Cite
|
Sign up to set email alerts
|

A esquistossomose urbana e a heterogeneidade social e epidemiológica da população do município de Campinas, São Paulo, Brasil

Abstract: This study deals with the relationship between schistosomiasis and urbanization, particularly the urbanization process experienced by cities in dependent capitalist countries, with large groups of people in precarious living conditions. Six hundred and ten notified autochthonous cases in Campinas during the period from 1970 to 1990 are analyzed through notification files with regard to patients socio-economic conditions. Autochthonous cases of schistosomiasis were demonstrated as having a more heterogeneous ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
14

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 1 publication
2
2
0
14
Order By: Relevance
“…Analyzing the Asano 16 report in relation to origin, she found that 48.27% of the patients with schistosomal myelitis came from the Metropolitan Region of Recife, and just 24.13% were from the Forest Zone (Zona da Mata). This information corroborates the urbanization process of schistosomiasis that has been described in the literature, occurring because of the disorganized growth of cities and migratory movements from the field, and almost always reflects the precariousness of the local sanitary-hygienic conditions 15,17 . The two other individuals came from two small endemic areas for schistosomiasis (the Agreste and the Sertão).…”
Section: Resultssupporting
confidence: 86%
“…Analyzing the Asano 16 report in relation to origin, she found that 48.27% of the patients with schistosomal myelitis came from the Metropolitan Region of Recife, and just 24.13% were from the Forest Zone (Zona da Mata). This information corroborates the urbanization process of schistosomiasis that has been described in the literature, occurring because of the disorganized growth of cities and migratory movements from the field, and almost always reflects the precariousness of the local sanitary-hygienic conditions 15,17 . The two other individuals came from two small endemic areas for schistosomiasis (the Agreste and the Sertão).…”
Section: Resultssupporting
confidence: 86%
“…A similar epidemiological situation has been described in various urban locations in Brazil 12,25,26 and worldwide 27,28 . In Pernambuco, coastal areas have been the target of the migratory flow of individuals parasitized with S. mansoni for decades, which, in search of better living conditions, settle on the city outskirts, where the lack of basic sanitation is maintained.…”
Section: Discussionsupporting
confidence: 76%
“…A forma como se darão as relações sociais, definirá o espaço construído no território, o que poderá ou não, viabilizar a ocorrência da doença (Barreto, 1982;Lima, 1995;Smith, 1988). O presente estudo mostrou que em vários municípios da região oeste do Estado, mais especificamente, naqueles que compreendiam áreas de expansão da fronteira agrícola, viabilizada pelo recurso do emprego de técnicas de irrigação de natureza pública e privada, a variação nas taxas de prevalência da infecção pelo S. mansoni foi baixa.…”
Section: Figuraunclassified